Emerging Pest Status of Jatropha curcus (L) In South India - Manoharan, T.; Ambika, S.; Natarajan, N.; Senguttuvan, K. (Indian Journal of Agroforestry, 2020)
Surveys conducted to explore the pests of Jatropha curcas (L.), their natural enemies and seasonal incidence revealed the presence of thirteen insects and two acarine pests. Of which, five were defoliators, while others were sucking pests. Among these, leaf webber Salebria morosalis (Saalm Uller), scutellerid bugs, Chrysocoris purpureus (Westw.) and Scutellera nobilis (Fabricius), thrips, Retithrips syriacus (Mayet) and yellow mite, Polyphagotarsonemus latus (Banks) were found predominantly. Except leaf webber, all other pests are polyphagous in nature. As much as eleven pests have been reported for the first time. Four parasitoids on leaf webber larvae, five egg parasitoids of scutelterid bug and six predatory spiders were found associated with the pests of J. curcas. The peak incidence of leafwebberwas during month of October, 2004 in all the survey locations. Natural parasitisation of leaf webber larvae by Trathala f1avo-orbitalis (Cameron) and Bracon hebetor (Say) was observed at Coimbatore and Mettuppalayam locations. B. hebetorÂ parasitism was not found at Chennimalai. Thrips were found only in Coimbatore and Mettuppalayam with a mean population of 4.39 and 4.04 per three leaves per plant, damaging to a mean level of9.22 and 10.23 per cent respectively.